Pilgrimage: Intrinsic Motivation and Active Behavior in the Eldery - Eichberg Henning; Kosiewicz Jerzy; Contiero Danilo (Sciendo, 2017)
Can intrinsic religious motivation have relevant effects on the motor activity of older people? How are processions and pilgrimages related to the dominant imagination of old age as a period of fatigue and gray hair, suffering and loneliness, retirement and rest - and of waiting: waiting for a call from a loved one, waiting for the visit of a good companion, or, finally, expecting the end of life?